Mechanochemical enzymatic resolution of N-benzylated-β3-amino esters - Pérez-Venegas, Mario; Reyes-Rangel, Gloria; Neri, Adrián; Escalante, Jaime; Juaristi, Eusebio (Beilstein Journal of Organic Chemistry, 2017)
The use of mechanochemistry to carry out enantioselective reactions has been explored in the last ten years with excellent results. Several chiral organocatalysts and even enzymes have proved to be resistant to milling conditions, which allows for rather efficient enantioselective transformations under ball-milling conditions. The present article reports the first example of a liquid-assisted grinding (LAG) mechanochemical enzymatic resolution of racemic β3-amino esters employing Candida antarctica lipase B (CALB) to afford highly valuable enantioenriched N-benzylated-β3-amino acids in good yields. Furthermore the present protocol is readily scalable.
Keywords: ball-milling; β3-amino acid; Candida antarctica lipase B; enzymatic resolution; mechanochemistry

(untitled) - Seebach, D.; Beck, A. K.; Capone, S.; Deniau, G.; Grošelj, U.; Zass, E. (Synthesis, 2009)

(untitled) - Steer, D. L.; Lew, R. A.; Perlmutter, P.; Smith, A. I.; Aguilar, M.-I. (Curr. Med. Chem., 2002)

(untitled) - Ton, J.; Mauch-Mani, B. (Plant J., 2004)

(untitled) - Farmer, L. J.; Clark, M. P.; Boyd, M. J.; Perola, E.; Jones, S. M.; Tsai, A.; Jacobs, M. D.; Bandarage, U. K.; Ledeboer, M. W.; Wang, T.; Deng, H.; Ledford, B.; et al. (ACS Med. Chem. Lett., 2017)

(untitled) - Seebach, D.; Beck, A. K.; Bierbaum, D. J. (Chem. Biodiversity, 2004)

(untitled) - Gentilucci, L.; De Marco, R.; Cerisoli, L. (Curr. Pharm. Des., 2010)

(untitled) - Zubrzak, P.; Williams, H.; Coast, G. M.; Issac, R. E.; Reyes-Rangel, G.; Juaristi, E.; Zabrocki, J.; Nachman, R. J. (Pept. Sci., 2007)

(untitled) - Magriotis, P. A. (Angew. Chem., Int. Ed., 2001)

(untitled) - Escalante, J.; González-Tototzin, M. A.; Aviña, J.; Muñoz-Muñiz, O.; Juaristi, E. (Tetrahedron, 2001)

Enantioselective Synthesis of β-Amino acids - Spiteller, P.; von Nussbaum, F. (β-Amino Acids in Natural Products, 2005)

(untitled) - Hoekstra, W. J.; Maryanoff, B. E.; Damiano, B. P.; Andrade-Gordon, P.; Cohen, J. H.; Costanzo, M. J.; Haertlein, B. J.; Hecker, L. R.; Hulshizer, B. L.; Kauffman, J. A.; Keane, P.; McComsey, D. F.; et al. (J. Med. Chem., 1999)

Handbook of Chiral Chemicals - Ager, D. J. (Synthesis of Non-Natural Amino Acids, 2006)

Amino Acids, Peptides and Proteins in Organic Chemistry - Bandala, Y.; Juaristi, E. (Recent Developments in the Synthesis of b-Amino Acids, 2009)

Enantioselective Synthesis of β-Amino Acids - Juaristi, E.; Soloshonok, V. A. (John Wiley and Sons, 2005)

(untitled) - Weiner, B.; Szymański, W.; Janssen, D. B.; Minnaard, A. J.; Feringa, B. L. (Chem. Soc. Rev., 2010)

(untitled) - Gedey, S.; Liljeblad, A.; Lázár, L.; Fülöp, F.; Kanerva, L. T. (Tetrahedron: Asymmetry, 2001)

(untitled) - Juaristi, E.; Quintana, D.; Escalante, J. (Aldrichimica Acta, 1994)

(untitled) - Juaristi, E.; López-Ruiz, H. (Curr. Med. Chem., 1999)

(untitled) - Abele, S.; Seebach, D. (Eur. J. Org. Chem., 2000)

(untitled) - Fülöp, F. (Chem. Rev., 2001)

(untitled) - Liu, M.; Sibi, M. P. (Tetrahedron, 2002)

(untitled) - Ma, J.-A. (Angew. Chem., Int. Ed., 2003)

(untitled) - Wenzel, A. G.; Jacobsen, E. N. (J. Am. Chem. Soc., 2002)

(untitled) - Ting, A.; Schaus, S. E. (Eur. J. Org. Chem., 2007)

(untitled) - Wilson, J. E.; Casarez, A. D.; MacMillan, D. W. C. (J. Am. Chem. Soc., 2009)

(untitled) - Meyer, D.; Marti, R.; Seebach, D. (Eur. J. Org. Chem., 2015)

(untitled) - Forró, E.; Fülöp, F. (Chem. – Eur. J., 2007)

(untitled) - Fitz, M.; Forró, E.; Vigóczki, E.; Lázár, L.; Fülöp, F. (Tetrahedron: Asymmetry, 2008)

(untitled) - Heck, T.; Seebach, D.; Steffen, O.; ter Wiel, M. K. J.; Kohler, H.-P. E.; Geueke, B. (ChemBioChem, 2009)

(untitled) - Weise, N. J.; Ahmed, S. T.; Parmeggiani, F.; Turner, N. J. (Adv. Synth. Catal., 2017)

(untitled) - Hernández, J. G.; Bolm, C. (J. Org. Chem., 2017)

(untitled) - Rodríguez, B.; Rantanen, T.; Bolm, C. (Angew. Chem., Int. Ed., 2006)

(untitled) - Declerck, V.; Nun, P.; Martinez, J.; Lamaty, F. (Angew. Chem., Int. Ed., 2009)

(untitled) - Bonnamour, J.; Métro, T.-X.; Martinez, J.; Lamaty, F. (Green Chem., 2013)

(untitled) - Baig, R. B. N.; Varma, R. S. (Chem. Soc. Rev., 2012)

(untitled) - Jones, W.; Eddleston, M. D. (Faraday Discuss., 2014)

(untitled) - Hernández, J. G.; Friščić, T. (Tetrahedron Lett., 2015)

(untitled) - Lawrenson, S. B.; Arav, R.; North, M. (Green Chem., 2017)

(untitled) - Hernández, J. G.; Juaristi, E. (Chem. Commun., 2012)

(untitled) - Schmidt, R.; Stolle, A.; Ondruschka, B. (Green Chem., 2012)

(untitled) - Hernández, J. G.; Macdonald, N. A. J.; Mottillo, C.; Butler, I. S.; Friščić, T. (Green Chem., 2014)

Ball Milling Towards Green Synthesis: Applications, Projects, Challenges - Machuca, E.; Juaristi, E. (Asymmetric Organocatalytic Reactions Under Ball Milling, 2015)

(untitled) - McKissic, K. S.; Caruso, J. T.; Blair, R. G.; Mack, J. (Green Chem., 2014)

(untitled) - Schmidt, R.; Burmeister, C. F.; Baláž, M.; Kwade, A.; Stolle, A. (Org. Process Res. Dev., 2015)

(untitled) - Friščić, T.; Trask, A. V.; Jones, W.; Motherwell, W. D. S. (Angew. Chem., Int. Ed., 2006)

(untitled) - Friščić, T.; Jones, W. (Cryst. Growth Des., 2009)

(untitled) - Hernández, J. G.; Frings, M.; Bolm, C. (ChemCatChem, 2016)

(untitled) - Hernández, J. G.; Ardila-Fierro, K. J.; Crawford, D.; James, S. L.; Bolm, C. (Green Chem., 2017)

(untitled) - Hernández, J. G.; Juaristi, E. (J. Org. Chem., 2010)

(untitled) - Polindara-García, L. A.; Juaristi, E. (Eur. J. Org. Chem., 2016)

(untitled) - Landeros, J. M.; Juaristi, E. (Eur. J. Org. Chem., 2017)

(untitled) - Rangel, H.; Carrillo-Morales, M.; Galindo, J. M.; Castillo, E.; Obregón-Zúñiga, A.; Juaristi, E.; Escalante, J. (Tetrahedron: Asymmetry, 2015)

(untitled) - Vaysse, L.; Ly, A.; Moulin, G.; Dubreucq, E. (Enzyme Microb. Technol., 2002)

(untitled) - Guizzetti, S.; Benaglia, M.; Bonsignore, M.; Raimondi, L. (Org. Biomol. Chem., 2011)

(untitled) - Bonsignore, M.; Benaglia, M.; Annunziata, R.; Celentano, G. (Synlett, 2011)

(untitled) - Péter, A.; Lázár, L.; Fülöp, F.; Armstrong, D. W. (J. Chromatogr. A, 2001)

(untitled) - Enders, D.; Wahl, H.; Bettray, W. (Angew. Chem., Int. Ed. Engl., 1995)